ANALISIS DAYA DUKUNG TANAH PADA PEMBANGUNAN JEMBATAN LAE MARSABAN DI SIDIKALANG KABUPATEN DAIRI (STUDI KASUS) - Yohanes Sibagariang; Esron Parulian Samosir (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2019)
In planning the lower structure data is needed regarding the characteristics of the soil and the structural loads acting on it. The research location is on a bridge located in Sidikalang, Dairi Regency, North Sumatra, which is called the Lae Marsaban Bridge on the Sumbul Pegagan Section - Parikki - Pangiringan Link. 117 STA. 143 + 000 in Dairi District. Examination of soil type is carried out visually to determine the value of carrying capacity of the soil. According to observations at the location that the condition of the soil was very hard and dense. Based on the results of a review of the Lae Marsaban Bridge Project, its carrying capacity has met the requirements based on the results of the sondir carried out. The foundation used is a sump foundation with a diameter of 2.5 meters and a depth of 8.4 meters, where the depth of hard soil is at 8.4 m. According to researchers, the implementation of the bridge is considered too excessive in terms of economic aspects. For this reason, more detailed and comprehensive research follow-up is needed.